Decolorization of hydrolysate of coconut meal using activated carbon after subcritical water treatment - Bunyakiat, Thapanee; Khuwijitjaru, Pramote (Food and Applied Bioscience Journal, 2017)
The hydrolysate obtained from subcritical water treatment of coconut meal exhibited dark brown color because of the degradation products from the treatment and hence interfered the purification process of the oligosaccharides from the hydrolysate. To solve this problem, the effectiveness of activated carbon for decolorizing the hydrolysate was studied. The activated carbon concentrations of 1–10% (w/v) and mixing times of 0–60 min were investigated. Color adsorption was determined by the change of an absorbance at 283 nm. The carbohydrate content was also measured after decolorization process. The results showed that the color adsorption increased as the activated carbon concentration was increased from 1 to 8% (w/v), but it was not significantly increased after 8% (w/v), indicated that 8% (w/v) was the optimal concentration for the decolorization. Additionally, the color adsorption did not change significantly after 20 min of mixing. The total carbohydrate content in the hydrolysate was not altered by the decolorization process. For the adsorption isotherm studies, three models (Langmuir, Freundlich, and Frumkin) were tested. The Langmuir model provided a better description of the process.